Strategies for controlling viral diseases of orchids in Vietnam - Dung, Nguyen Xuan; Thao, Nguyen Thi Thanh; Xo, Duong Hoa (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2020)
Orchids are one of the most important flowering plants in Vietnamese urban agriculture. During the last decade, the orchid cultivation area has expanded significantly and this has led to the increase of the growers' income. The orchid - virus diseases are causing serious damage to orchid production and quality while the treatment hasn't yet been shown. Conventional approaches to control virus spread are time - consuming and costly, however ineffective. In order to control this disease more effectively, it is necessary to establish efficient strategies employing advanced techniques of plant biotechnology. In this report, we present the outputs of our current strategy for managing the viral disease in orchids, including virus detection using the RT - PCR, virus - free orchid micropropagation, meristerm culture for the recovery of virus - infected plants, and development of virus - resistant orchids using RNA interference (RNAi) technology. In addition, the feasibility, effectiveness and prospects of the control strategies for orchid viruses in Vietnam are also discussed.